Best-Worst Scaling to Prioritize Outcomes Meaningful to Caregivers of Youth with Mental Health Multimorbidities: A Pilot Study. Issue 2 (February 2018) - Camelo Castillo, Wendy; Ross, Melissa; Tariq, Saad; dosReis, Susan
Abstract: Objective: Health care decision-making for youth with mental health multimorbidity is guided by outcomes that are considered most meaningful and important. The study objective was to pilot test a best-worst scaling (BWS) instrument designed to assess trade-offs among caregiver-defined, meaningful health care outcomes. Methods: A BWS was designed with continuous stakeholder involvement to elicit caregiver-defined outcomes in 4 domains: school, behavioral, social, and independence. Four attributes were identified for each outcome domain, for a total of 16 attributes. Using a balanced incomplete block design, a BWS instrument was developed with 16 choice task questions displaying 6 attributes at a time. A convenience sample was selected from Maryland caregivers of children who were 21 years old or younger and had a developmental delay and a comorbid mental health condition. Participants completed a survey that included demographics and the BWS instrument. Conditional logit was used to estimate utility scores and 95% confidence intervals (CI) for each attribute, which were ranked in order of importance. Attribute statements were refined after a respondent debriefing session. Results: A total of 38 caregivers participated in the pilot study. Child safety to self was the most important outcome (1.01, CI, 0.78–1.24). This was followed by securing support for an Individualized educational plan in school (0.77, CI, 0.54–1.01) and the child being able to stay in school all day (0.53, CI, 0.29–0.77). Conclusion: BWS scenarios that resemble real-life decision-making can be a useful tool to identify preferences for health care outcomes. Abstract : This article has supplementary material on the web site: www.jdbp.org.